Understanding History and Culture in 19th Century England: Contributions from Dickens, Thackeray, and Eliot - Jakovljević, Mladen M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Students in programmes of English studies learn about history from historical textbooks, which provide a broad overview but lack detail. These texts prioritise a selection of significant events and collective narratives, neglecting the experiences of individuals. Consequently, the picture presented by textbooks remains overly general. Literature, conversely, offers a rich tapestry of individual stories that, when combined with historical textbooks, encourage students to link general facts with personal narratives. This helps students arrive at a deeper understanding of historical events and cultural circumstances and their impact on individual lives. The combined approach facilitates students’ ability to imagine the daily realities of the past with a nuanced appreciation of both continuities and changes across time. William Makepeace Thackeray’s Vanity Fair, Charles Dickens’s Great Expectations, and George Eliot’s The Mill on the Floss exemplify how instructors can leverage the complementary strengths of historical textbooks and Victorian novels to cultivate a more comprehensive understanding of the past, surpassing the limitations of either discipline in isolation.
Keywords: Victorian era; Victorian novel; English studies; Charles Dickens; William M. Thackeray; George Eliot